Multi-Modal Transportation Advisor system - Ferreira, J. C.; Filipe, P.; Silva, A. (2011 IEEE Forum on Integrated and Sustainable Transportation Systems, 2011)
The current work deals with the problem of growing population in the cities and the associated mobility problems. For this problem it is proposed a Multi-Modal Transportation Advisor system, based on the integration from different data sources such as public transportation systems, car and bike sharing or car pooling. Taking into account real time traffic information the system shows best option for a user goes from point A to a point B and calculates the associated trip cost. This is part of the European Project START, where we show the contribution of a public transportation ontology for different DB integration and a best path advisor based on an appropriate Dijkstra's algorithm implementation.